Motherhood in Herland - Pechová, Adéla (Univerzita Pardubice, 2023)
This thesis deals with different feminist perceptions of motherhood and its reflection in the novel Herland by Charlotte Perkins Gilman. The first part offers a brief historical overview of American women writers, and it outlines feminism with a special emphasis on motherhood. The second part examines the selected novel and explores specific issues connected to motherhood and their close relation to feminism.
Mateřství v románu Herland
Keywords: feminismus; mateřství; ženy; USA; patriarchát; utopie; feminism; motherhood; women; USA; patriarchy; utopia